Process intensification of membrane system for crude palm oil pretreatment - Iyuke, Sunny Esayegbemu; Ahmadun, Fakhru'l-Razi; Abd. Majid, Rusnani (2004)
The pretreatment of crude palm oil (CPO) samples with the aim of moving from the usual huge refinery plant to a more process integrated membrane module at ultrascale size was studied. The study was carried out using conventional refining, microfiltration, and ultrafiltration processes. Reduction of phosphorus fur the membrane-permeate of 43.3% was higher than that of bleached oil of 34.4%. The results show that the average slurry volume after about 22-min runs for membrane with ore size of 0.45 μm, 0.2 μm, 50 nm and 20 nm, and the average slurry volumes are 0.05, 0.09, 0.13, and 0.18m3 respectively.